Human Saliva-Mediated Hydrolysis of Eugenyl-β-D-Glucoside and Fluorescein-di-β-D-Glucoside in In Vivo and In Vitro Models - Mariusz Dziadas; Adam Junka; Henryk Jeleń (Biomolecules, 2021)
Eugenyl-β-D-glucopyranoside, also referred to as Citrusin C, is a natural glucoside found among others in cloves, basil and cinnamon plants. Eugenol in a form of free aglycone is used in perfumeries, flavourings, essential oils and in medicinal products. Synthetic Citrusin C was incubated with human saliva in several in vitro models together with substrate-specific enzyme and antibiotics (clindamycin, ciprofloxacin, amoxicillin trihydrate and potassium clavulanate). Citrusin C was detected using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Citrusin C was completely degraded only when incubated with substrate-specific A. niger glucosidase E.C 3.2.1.21 (control sample) and when incubated with human saliva (tested sample). The addition of antibiotics to the above-described experimental setting, stopped Citrusin C degradation, indicating microbiologic origin of hydrolysis observed. Our results demonstrate that Citrusin C is subjected to complete degradation by salivary/oral cavity microorganisms. Extrapolation of our results allows to state that in the human oral cavity, virtually all β-D-glucosides would follow this type of hydrolysis. Additionally, a new method was developed for an in vivo rapid test of glucosidase activity in the human mouth on the tongue using fluorescein-di-β-D-glucoside as substrate. The results presented in this study serve as a proof of concept for the hypothesis that microbial hydrolysis path of β-D-glucosides begins immediately in the human mouth and releases the aglycone directly into the gastrointestinal tract.